2021
DOI: 10.1186/s12981-021-00336-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of virological failure among people living with HIV receiving first line antiretroviral treatment in Myanmar: retrospective cohort analysis

Abstract: Background Progress toward the global target for 95% virological suppression among those on antiretroviral treatment (ART) is still suboptimal. We describe the viral load (VL) cascade, the incidence of virological failure and associated risk factors among people living with HIV receiving first-line ART in an HIV cohort in Myanmar treated by the Médecins Sans Frontières in collaboration with the Ministry of Health and Sports Myanmar. Methods We cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…Despite the long waiting time for a first VL, 95% of patients who had a first VL done had a VL below1000 copies/ml. This is also high compared to other reports in resource-limited settings in Africa and Asia, including Myanmar, in which suppression rates were found between 72 and 91% [4,9,[25][26][27][28][29]. As treatment adherence was probably good in our cohort, the long delay in VL testing did not have a large negative impact on viral load results.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Despite the long waiting time for a first VL, 95% of patients who had a first VL done had a VL below1000 copies/ml. This is also high compared to other reports in resource-limited settings in Africa and Asia, including Myanmar, in which suppression rates were found between 72 and 91% [4,9,[25][26][27][28][29]. As treatment adherence was probably good in our cohort, the long delay in VL testing did not have a large negative impact on viral load results.…”
Section: Discussioncontrasting
confidence: 40%
“…If the second VL is also above 1000 copies/mL despite EAC, virological failure is confirmed and prompt switch to a second-line regimen is indicated [3]. Though VL is regularly measured in developed countries, access to VL tests is still very limited in many low resource settings and this leads to delayed switching to second-line ART [4][5][6][7][8]. The mostly centralized VL testing demands sophisticated and expensive facilities, equipment, and skilled technicians, making it difficult and impractical to scale up.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Henan region of China showed that long-term second-line ART was effective (31). Another study in Myanmar showed that 66.5% patients with virologic failure were switched to a second-line ART regimen within 6 months after confirmed virologic failure (32). We found that secondline ART was useful for reducing the overall cohort mortality rate, and that among patients on second-line ART regimens, the mortality rates did not differ significantly according to the baseline VL.…”
Section: Last Art Regimenmentioning
confidence: 99%
“…This is because VF is the result of multiple and complex factors that go beyond treatment efficacy such as poor adherence, inadequate care or access to healthcare, and other sociodemographic factors and contextual variables. 16 – 18 …”
Section: Introductionmentioning
confidence: 99%
“…This is because VF is the result of multiple and complex factors that go beyond treatment efficacy such as poor adherence, inadequate care or access to healthcare, and other sociodemographic factors and contextual variables. [16][17][18] While an early study conducted in a third-level hospital in Mexico City in 2010 found that the probability of VF was 20% at 48 months after ART initiation and was higher among youth (individuals younger than 30 years old), 14 this study was published before the 2014 changes in clinical guidelines. In addition, the determinants of VF have not been explored in Mexico and the 2014 policy changes have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%